The nature of human behavior in the distinction of good environmental performance: a constructivist essay on having and being (Research, Society and Development, 2022)
Based on the constructivist theory of learning and the principles of physics, this article aims to present theoretical and methodological contributions to the evaluation of environmental performance, based on the quality of human performance in the use of the media. Therefore, environmental performance is understood as the result of learning processes and the amplification of intelligence potential, which explains the individual-environment relationship. Based on bibliographic and documentary research, mobilizing Piaget's psychogenetic theory and Prigogine's theory of dissipative structures, this article presents the Environmental Performance Index (IDA) as a result of these studies, which, in addition to being an analytical tool, is proposed as an enhancer for better uses of resources. The IDA, by pointing out an adequate attribute of environmental performance, presents itself as a facilitator in understanding the implications arising from the use of means and motivator in the search for the improvement of its performance and, consequently, for its human differentiation. Thus, based on the methodological instrument, one could assess who performs well, in essence, reward those who use the means well and not only punish. This possibility of valuing the good use of resources could, for example, complement as tools for evaluating public policies on environmental services.